Animal Protection in Indonesia: An Evaluation of Law Enforcement Based on the Principles of the Universal Declaration of Animal Rights - Martha Claudya Pattiasina; Sharon Angelia; Mardian Putra Frans (Bacarita Law Journal, 2026)
Weak law enforcement against perpetrators of animal abuse in Indonesia. The purpose of the study isto analyze the suitability of law enforcement practices in Indonesia for perpetrators of violence and animal abuse with the principles of the Universal Declaration of Animal Rights (UDAR). The research method used is normative legal research with a legislative approach, case studies, conceptual, and comparative law. The results of the study show that Indonesian laws and regulations are not in line with the principles of UDAR, which in fact still classify animals as mere objects. The criminal sanctions given are too light and the law enforcement is inconsistent. Analysis of the three court decisions shows that there is a disparity between the level of cruelty and the punishment imposed, which is generally in the form of probation or short imprisonment. This study recommends a revision of the legal framework by toughening sanctions, the drafting of a comprehensive animal welfare law, the adoption of UDAR principles, and the establishment of an Independent Animal Welfare Commission.